Construction of Biholomorphic Convex Mappings of Order α on Bpn. (8th April 2014) - Liu, Ming-Sheng; Yang, Fengying; Kou, Kit Ian; Huang, Changqin
Abstract : Some sufficient conditions for biholomorphic convex mappings of order α on the Reinhardt domain B p n in C n are given; from that, criteria for biholomorphic convex mappings of order α with particular form become direct. As applications of these sufficient conditions, some concrete biholomorphic convex mappings of order α   on B p n are provided.